Distal femur arthroplasty for non-union distal femur fracture with failed osteosynthesis in osteoporotic octogenarian: a case report with literature review - Tomar, Lavindra; Govil, Gaurav; Dhawan, Pawan (International Journal of Research in Orthopaedics, 2022)
Distal femur fractures (DFF) in the elderly have high morbidity and management challenges. The low energy trauma commonly presents significant fracture comminution, osteoporosis, pre-existing knee arthritis, co-morbid medical conditions affecting the union, weight-bearing potential and rehabilitation with profound functional disability. An octogenarian presented with a failed osteosynthesis resulting in non-union of a distal femur fracture compounded by osteoporosis and knee arthritis. He had been non-ambulatory with a painful, deformed knee. Management with a single-stage removal of the distal femur locked plate constructs and the defect reconstruction with the distal femur arthroplasty (DFA). The outcome was a pain-free weight-bearing mobilization with a functional range of knee motion. The surgical management in the elderly for the displaced intra-articular distal femur fractures is to restore the limb length and articular congruence for a functional knee. Fixation with either a distal femur locking plate or an intramedullary nail has a propensity for non-union, malunion, knee stiffness, and failed fixation. Salvage procedure gives good functional outcomes in failed osteosynthesis with DFA. The arthroplasty allows an immediate pain-less weight-bearing potential with improved ambulatory status and quality of life. The single-stage procedure in the elderly can regain a stable, functional knee joint.